EVALUASI PROGRAM BANTUAN LANGSUNG TUNAI (BLT) BAGI KELUARGA MISKIN DI KOTA SURABAYA - Danu Firman Cahya Sysnanda; Purwasih Diansiwi; Farhan Bhagaskara Handoko (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
Poverty remains one of the most pressing social issues and continues to be a major challenge for both central and local governments. To address this problem, the Surabaya City Government has implemented the Direct Cash Assistance (BLT) program, targeting poor households that have not previously received assistance from other programs. This study aims to evaluate the implementation of the BLT program in Kapasmadya Baru Village, Tambaksari District, Surabaya City, which is among the areas with the highest number of poor households. The research employed a qualitative approach with a descriptive technique, using in-depth interviews and supporting literature studies. The evaluation was conducted based on six indicators from William N. Dunn’s policy evaluation theory: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings reveal that the BLT program has been fairly helpful for poor households in meeting basic needs such as education and daily consumption. However, its implementation still faces challenges, particularly in terms of targeting accuracy, data updating, and equitable distribution of aid. The government needs to strengthen data verification mechanisms as well as enhance transparency and public outreach to ensure that assistance is delivered more fairly and effectively.